Bioavailability of dissolved organic matter varies with anthropogenic landcover in the Upper Mississippi River Basin. (1st February 2023) - Vaughn, Derrick R.; Kellerman, Anne M.; Wickland, Kimberly P.; Striegl, Robert G.; Podgorski, David C.; Hawkings, Jon R.; Nienhuis, Jaap H.; Dornblaser, Mark M.; Stets, Edward G.; Spencer, Robert G.M.
Highlights: Examined landcover impacts on stream dissolved organic matter (DOM) bioavailability. Streams draining urban lands contained more bioavailable DOM than agricultural lands. Forested streams had high organic carbon concentrations but lowest bioavailability. Demonstrated relationship between aliphatic compound abundances and bioavailability. Landcover does not impact what compounds are lost during bioincubation. Abstract: Anthropogenic conversion of forests and wetlands to agricultural and urban landcovers impacts dissolved organic matter (DOM) within streams draining these catchments. Research on how landcover conversion impacts DOM molecular level composition and bioavailability, however, is lacking. In the Upper Mississippi River Basin (UMRB), water from low-order streams and rivers draining one of three dominant landcovers (forest, agriculture, urban) was incubated for 28 days to determine bioavailable DOC (BDOC) concentrations and changes in DOM composition. The BDOC concentration averaged 0.49 ± 0.30 mg L −1 across all samples and was significantly higher in streams draining urban catchments (0.72 ± 0.34 mg L −1 ) compared to streams draining agricultural (0.28 ± 0.15 mg L −1 ) and forested (0.47 ± 0.17 mg L −1 ) catchments. Percent BDOC was significantly greater in urban (10% ± 4.4%) streams compared to forested streams (5.6% ± 3.2%), corresponding with greater relative abundances of aliphatic and N-containing aliphatic compounds in urban streams. Aliphatic compound relative abundance decreased across all landcovers during the bioincubation (average -4.1% ± 10%), whereas polyphenolics and condensed aromatics increased in relative abundance across all landcovers (average of +1.4% ± 5.9% and +1.8% ± 10%, respectively). Overall, the conversion of forested to urban landcover had a larger impact on stream DOM bioavailability in the UMRB compared to conversion to agricultural landcover. Future research examining the impacts of anthropogenic landcover conversion on stream DOM composition and bioavailability needs to be expanded to a range of spatial scales and to different ecotones, especially with continued landcover alterations. Graphical abstract: Image, graphical abstract